Rancangan Sekolah Taman Kanak-Kanak Anti Bullying sebagai Penanaman Akhlaqul Karimah pada Anak Usia Dini - Azizah, Farah (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
Bullying has a huge impact on children who become victims, such as low self-esteem, anxiety, and depression. Therefore, there needs to be prevention carried out by schools to overcome bullying in the school environment. In kindergarten, it is hoped that the cultivation of moral values can be planted and fertilized as well as possible and as early as possible so that children have akhlaqul karimah. Moreover, the kindergarten period is a golden age period where in this age period the cultivation of good values and personality norms can determine how the child's behavior patterns will be in the future. The type of research that will be used in this research is literature review. The data analysis used has 4 stages, namely: method planning, data collection, and analysis and synthesis. The results of this study show that the design of an anti-bullying kindergarten must incorporate aspects of Inclusive Physical Design, Collaborative Play, Anti-bullying education program, Teacher and supervisor training, Counseling Support, Parent Participation, and Use of Educational Technology